Determination of synthropy index for justification measures for early diagnosis and prevention of non-communicable diseases - Peresypkina, Tetiana; Butenko, Antonina; Peresypkina, Anna (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. The spread of non-communicable diseases among pediatric population focuses attention of the scientific community on the search for effective mechanisms for early diagnostic of diseases and the introduction of appropriate preventive measures. According to the Center for Medical Statistics, the prevalence of diseases among adolescents is 2177.7 ‰ (in 2017), which may indicate the presence of several diseases in one adolescent and includes preventive measures to the category of immediate. The aim is to determine syntropic diseases and morpho-functional disorders among school-age children at the stages of medical preventive examinations. Materials and methods: M. von Pfaundler’s formula was used to calculate the index of syntropy (joint manifestation of diseases) on the basis of data from the evaluation of medical examinations of students during studying, at first to ninth grades. An index above 3.0 was chosen for analysis, which indicates a high syntropy of diseases. Syntropy indices are calculated for boys and girls. Results. The method of determining syntropic diseases is widely used by the Ukrainian scientific community [3, 4, 5]. The results of the study showed common syntropic combinations with a high index of syntropy throughout the period of study in primary and secondary school. Inherent for the boys were: functional disorders of the biliary tract, hypertrophy of the tonsils, posture disorders or functional weakness of the feet. For girls, common combinations were functional disorders of the biliary tract, hypertrophy of the tonsils and disorders of the neurological spectrum (neurasthenia, cerebrospinal fluid hypertension, vegetative - vascular dystonia). «Marker» diseases that require an expansion of the range of diagnostic and preventive measures for girls are FRBT, deviations of the nervous system. For boys with functional disorders of the biliary tract, puberty, or musculoskeletal disorders, additional diagnostic measures are required. Conclusions. The current Order of the Ministry of Health of Ukraine on medical care for students of general secondary education (medical preventive examinations) provides only examination by a pediatrician, other specialists - according to the indications. Therefore, given the high syntropy of certain diseases, it is advisable to focus the attention of primary care professionals in conducting medical preventive examinations among children of primary school years and twelve to thirteen years to identify possible combined pathology and increase the level of knowledge of health professionals in the pre-medical stage of medical preventive examinations in order to identify diseases and morpho-functional abnormalities among school-age children and to introduce timely preventive measures.